Vous avez dit « Paysage » ? - Catherine Chomarat-Ruiz (Projets de Paysage)
Based on the metaphorical use of the term "landscape" in science, especially in the expression "Materials - Landscapes," the article intends to capture some invariants and new characterizations of this scientific object. It is, indeed, to show the epistemological interest of a "detour" by other scientific disciplines than history to renew the field of landscape studies and consider original way of responding to research programs grouped under the heading of "Nature in the city».